Fast formation of aligned high-aspect ratio TiO2 nanotube bundles that lead to increased open circuit voltage when used in dye sensitized solar cells - Jha, Himendra; Roy, Poulomi; Hahn, Robert; Paramasivam, Indhumati; Schmuki, Patrik (Electrochemistry Communications, 2011)
Ultrafast formation of high-aspect ratio titanium dioxide nanotube is carried out by the rapid-breakdown-anodizing technique using a two compartment electrochemical cell. The change in surface morphology of the titanium substrate during anodization, and physical parameters such as pH and temperature are investigated. Under optimized conditions, aligned TiO2 nanotube powder is obtained that beneficially can be used in dye-sensitized solar cells. Solar cell constructed using the nanotube powder can show a significantly higher open circuit voltage than when constructed with commercially available nanoparticles.
EAM Import::2019-03-14